2011
DOI: 10.2298/vsp1106489s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of use of riboflavin and ultraviolet light for pathogen inactivation on quality of platelet concentrates

Abstract: Platelet concentrates inactivated by riboflavin and UV rays (Mirasol PRT sistem, Caridian BCT, USA) keep all the characteristics assessed by the Guide to the preparation, use and quality assurance of blood components (Council of Europe), during the whole storage period (five days). The obtained data were correlated with existing up to date literature and demonstrated that Mirasol treated platelets were safe and could be incorporated effectively in the routine blood bank and transfusion setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Preclinical studies have revealed the effectiveness of reduction in infectivity of some viruses, including HIV-1, bovine viral diarrhea virus (BVDV), a model for HCV; single-stranded RNA virus), and pseudorabies virus, as well as bacteria in blood products [175178]. …”
Section: Photodynamic Therapy As An Anti-infectivementioning
confidence: 99%
“…Preclinical studies have revealed the effectiveness of reduction in infectivity of some viruses, including HIV-1, bovine viral diarrhea virus (BVDV), a model for HCV; single-stranded RNA virus), and pseudorabies virus, as well as bacteria in blood products [175178]. …”
Section: Photodynamic Therapy As An Anti-infectivementioning
confidence: 99%